1994
DOI: 10.1002/star.19940460807
|View full text |Cite
|
Sign up to set email alerts
|

Some Studies on Starch Carbamate

Abstract: Starch carbamate was prepared by reacting maize starch with urea using solid state technique. The different factors affecting this reaction were studied. These factors include urea concentration, type of starch, reaction and duration. The carbamate extent and carbamation reaction efficiency (%) were traced by estimating the nitrogen content of the reaction product. Solubility, viscosity and total ester content of starch carbamate samples were estimated. The carbamate extent increases by increasing urea concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 17 publications
1
20
0
2
Order By: Relevance
“…These are also able to crosslink by further reactions with elimination of ammonia (see Figure 2). It is known that high temperatures and long reaction times promote this kind of condensation reactions [21,22]. As side-products, unreacted urea, phosphating agents, and biuret from urea decomposition remain in the product which can be washed out by dialysis, filtration, and precipitation procedures [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are also able to crosslink by further reactions with elimination of ammonia (see Figure 2). It is known that high temperatures and long reaction times promote this kind of condensation reactions [21,22]. As side-products, unreacted urea, phosphating agents, and biuret from urea decomposition remain in the product which can be washed out by dialysis, filtration, and precipitation procedures [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…As side-products, unreacted urea, phosphating agents, and biuret from urea decomposition remain in the product which can be washed out by dialysis, filtration, and precipitation procedures [23][24][25]. So far, polysaccharide derivatives from phosphate/urea systems were previously discussed as water absorbing hydrogel for waste water treatment and applications in pharmacy, food industry, So far, polysaccharide derivatives from phosphate/urea systems were previously discussed as water absorbing hydrogel for waste water treatment and applications in pharmacy, food industry, cosmetics, and agriculture [18,22,27]. There is little data on flame retardant additives processed and tested through this method [28].…”
Section: Introductionmentioning
confidence: 99%
“…The mass percentages of N changed from 10.28% before hydrolysis to 1.82% after hydrolysis, and those of O changed from 33.82% before hydrolysis to 61.39% after hydrolysis. The −COO ‐ content of hydrolyzed polymers is dependent on the amount of NaOH, and it has been reported that the carboxyl content increase with increasing NaOH concentration to reach a maximum and then decrease …”
Section: Resultsmentioning
confidence: 99%
“…It has lower crystallinity than cellulose, and is relatively easy to be chemically modified. Use of starch as a raw material for SAPs has been reported, which includes hydrolyzed starch–polyacrylonitrile graft copolymer, [ 4 ] hydrolyzed product of starch–polyacrylonitrile physical mixture, [ 5 ] crosslinked carboxymethyl starch, [ 6,7 ] crosslinked oxidized starch, [ 8 ] crosslinked starch phosphate, [ 9,10 ] crosslinked starch carbamate, [ 11 ] and starch phosphate carbamate (SPC). [ 12,13 ]…”
Section: Introductionmentioning
confidence: 99%